IMPLEMENTASI DIPONEGORO LITERASI DIGITAL (DIPOLITA) DALAM MENDUKUNG PEMBELAJARAN DAN RISET ILMIAH - Sri Endah Pertiwi; Suwondo Suwondo; Haryani Haryani; Enny Anggraeny; Romdha Anugrahani (UPT Perpustakaan dan Undip Press, 2024)
Abstract :Diponegoro Digital Literacy (DIPOLITA) is a platform for digital literacy activities by the UPT Library and Undip Press, which accommodates library activities/programs through the stages of achieving the Dipolita library program implemented in the annual development roadmap. The goal of Dipolita is to enhance literacy for the academic community of Undip through various activities specifically designed to improve understanding and skills in using digital information sources. The Dipolita study method involves conducting feasibility and needs analysis, analyzing and determining the requirement document, using best practices, designing, measuring and tracking progress, developing various digital collection ecosystems, integrating various application ecosystems within Dipolita, conducting trials, and implementing practices in stages. Conclusion: Diponegoro Digital Literacy with 7 features, namely Diopac, Ezprozy, Digilib, Schedule, webinar, Moodula, and Testtime, has improved the digital literacy of the academic community at Undip and the use of digital information sources. Dipolita becomes a platform that facilitates users in information literacy activities, thereby enhancing the role of the Library UPT and Undip Press in learning and scientific research. Keywords: application, digital literacy, Dipolita, information literacy, library. Abstrak :Diponegoro Literasi Digital (DIPOLITA) merupakan wadah kegiatan literasi digital UPT Perpustakaan dan Undip Press yang mewadahi kegiatan/program perpustakaan melalui tahapan pencapaian program Dipolita perpustakaan yang diimplementasikan dalam road map pembangunan tiap tahun. Tujuan Dipolita yaitu meningkatkan literasi bagi sivitas akademika Undip melalui berbagai kegiatan yang dirancang khusus untuk meningkatkan pemahaman dan ketrampilan dalam menggunakan sumber informasi digital. Metode kajian Dipolita yaitu melakukan analisis kelayakan dan kebutuhan, analisis dan tentukan requirement document, gunakan best practices, desain, mengukur dan melacak perkembangan, pengembangan berbagai ekosistem koleksi digital, mengintegrasikan berbagai ekosistem aplikasi dalam Dipolita, melakukan uji coba, praktik penerapan bertahap. Kesimpulan, Diponegoro Literasi Digital dengan 7 fitur yaitu Diopac, Ezprozy, Digilib, Schedule, webinar, Moodula dan Testtime telah meningkatkan literasi digital sivitas akademika Undip dan penggunaan sumber informasi digital. Dipolita menjadi laman yang memudahkan pemustaka dalam kegiatan literasi informasi sehingga meningkatkan peran UPT Perpustakaan dan Undip Press dalam pembelajaran dan riset ilmiah. Kata kunci: aplikasi, dipolita, literasi digital, literasi informasi, perpustakaan.